(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Lepidorbitoides bisambergensis is characterised by having a ‘quadriserial’ embryo without any chamberlet directly arising from the deuteroconch and is a very diagnostic and common species in Lower Maastrichtian flysch successions in Anatolia. Some populations of this species present an early ontogenetic morphologic feature which is characterised by distinctly asymmetric early chamber arrangement recognised in the horizontal sections. This asymmetry is mainly caused by the pronounced difference in the size of auxiliary chamberlets which rest on both, protoconch and deuteroconch and also enhanced by the development of unequal number of chamberlets in the series arising from these auxiliary chamberlets on the protoconchal side. These asymmetric specimens are commonly identified in stratigraphic horizons below the symmetric ones after the introduction of a new auxiliary chamberlet and progressively replaced by symmetric ones in the younger populations. Asymmetric "quadriserial" specimens representing the early phylogenetic stage of L. bisambergensis described in the stratigraphic horizons corresponding to G. havanensis and G. aegyptiaca (?) zones are thought to deserve a particular taxonomic status and are attributed to Lepidorbitoides bisambergensis asymmetrica Özcan & Özkan-Altiner, 1999a.